2012
DOI: 10.1039/c1mt00118c
|View full text |Cite
|
Sign up to set email alerts
|

A possible mechanism for combined arsenic and fluoride induced cellular and DNA damage in mice

Abstract: Arsenic and fluoride are major contaminants of drinking water. Mechanisms of toxicity following individual exposure to arsenic or fluoride are well known. However, it is not explicit how combined exposure to arsenic and fluoride leads to cellular and/or DNA damage. The present study was planned to assess (i) oxidative stress during combined chronic exposure to arsenic and fluoride in drinking water, (ii) correlation of oxidative stress with cellular and DNA damage and (iii) mechanism of cellular damage using I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(31 citation statements)
references
References 62 publications
(69 reference statements)
1
30
0
Order By: Relevance
“…Some recent finding demonstrates that depletion of antioxidant components and higher mutagenic DNA breakages in arsenic-exposed human result in necrosis and carcinogenesis [2,3]. The liver, being the metabolic port of entry, is the major target of arsenic toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…Some recent finding demonstrates that depletion of antioxidant components and higher mutagenic DNA breakages in arsenic-exposed human result in necrosis and carcinogenesis [2,3]. The liver, being the metabolic port of entry, is the major target of arsenic toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…It is known that xenobiotic interaction may increase or decrease the toxic effect of one or many substances. [10][11][12] Therefore, the effects of AgNPs and F co-exposure on cell viability, oxidative stress, and inflammation were evaluated in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…Se-As interactions have also been reported (Davis et al, 2000) to produce alterations in the methylated pathway and to alter DNA methylation in CaCo2 cells in vitro. Studies by Flora et al (2012) in mice examined the combined oxidative stress effects of As and fluoride administered in drinking water for 28 weeks. These investigators found evidence of oxidative damage to a number of molecular DNA and protein parameters from coexposure to these elements, but effects were not synergistic.…”
Section: Arsenic and Other Metalsmentioning
confidence: 99%